2009
DOI: 10.1177/1076029609336855
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Hydroxyethyl Starch (HES) Formulations on Fibrinogen Measurement in HES-Diluted Plasma

Abstract: The study showed that all HES solutions more or less impaired the fibrinogen measurement with the photo-optical method. In particular, overestimation with CLS-low may prevent timely fibrinogen replacement in major blood loss. Hydroxyethyl starch concentration appears to be more relevant for this effect than its molecular size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
1
18
0
3
Order By: Relevance
“…[30][31][32] Starches have also been shown to affect measurement of plasma fibrinogen concentration with the Clauss method. 33 Therefore, the use of HES 130/0.4 in our population may have contributed to the lower MCF cut-off value. Alternatively, it may also have influenced the cut-off value we observed for plasma fibrinogen concentration.…”
Section: Discussionmentioning
confidence: 90%
“…[30][31][32] Starches have also been shown to affect measurement of plasma fibrinogen concentration with the Clauss method. 33 Therefore, the use of HES 130/0.4 in our population may have contributed to the lower MCF cut-off value. Alternatively, it may also have influenced the cut-off value we observed for plasma fibrinogen concentration.…”
Section: Discussionmentioning
confidence: 90%
“…These studies showed that FIB was overestimated by >50% and >100% with 30% and 50% dilution, respectively. Notably, in this context the concentration of HES appears to be more important than molecular size [39,40]. …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that fibrinogen levels were overestimated in the present study, because hydroxyethyl starch had been administered. [48][49][50] The method used to determine the incidence of DIC in this animal study was based on clinical judgment, with consideration of the International Society on Thrombosis and Hemostasis criteria, which were designed for humans. 35 There are no established diagnostic criteria for porcine DIC, but the clinical signs of DIC were clear in this study.…”
Section: Discussionmentioning
confidence: 99%